Perancangan Fasilitas Tunggu dan Advertising di Pusat Perbelanjaan Mall - Santoso, Joshua Alim; Kusumarini, Yusita; suprobo, filipus priyo (Intra, 2016)
Shopping center mall which is known as a place that containts all kinds of products to market and received by the visitors as a place to buy needs and recreation. The visitors often come just to accompany their partners without any other intentions. When they feel tired and bored but their partner is still walking around, they will wait. This design is intended to find two needs from the visitors who waits and the shopping center mall’s administrator. The initial observation which was done is intended to gain the data of needs, habit, and characters of the visitors in the situation that make them waits. Observation is also done to gain data from the availability of waiting area in the shopping center mall, which is bench. The results of the observation becomes the reference of some case studies which are announced to the public to know the habits of the users in choosing sitting position which has been prepared by the mall’s developer. Besides that, the mall’s developer have other needs and main purpose which is money oriented profits. So in this design, with adding commercial elements as the main point in this waiting activity, whereas even if the visitors are just waiting, they can optimally interact. The result of the thinking process to combine both needs, advertising, information center, also online shopping facility become something that is a huge advantage for the mall and also become one of the waiting facility for the visitors to spend their time.